Characteristics of the Qur'anic Manuscript from Menoreh Magelang - Hanifatul Asna (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This article focuses on Quranic manuscripts that are believed to be attributed to Prince Diponegoro. This Quranic manuscript stored in Magelang and was brought by Prince Diponegoro during the Java War (1825-1830 AD), which he led. Previous researchers have studied Prince Diponegoro’as a religious figure, but no one has examined Quranic manuscripts that credited to his legacy. Through the Philology approach, this paper shows authentic Quranic manuscripts originating from the time of Prince Diponegoro's life. Illumination with Javanese floral style in the manuscript has similarities with the Quranic manuscript collection of the Pura Pakualaman museum with a watermark that shows paper production around 1823-1824 AD. The content of the manuscript strengthened the data on the use of Imla'i rasm, and reading symbols in the Manuscripts shows the characteristics of the development of Qur'anic science in the 19th century.